Penambahan Ekstender Madu Dalam Proses Penyimpanan Sperma Beku Terhadap Motilitas Dan Viabilitas Spermatozoa Ikan Komet (Carassius auratus auratus) [Additions Extender Honey In Frozen Sperm Storage Process Against Sperm Motility And Viability Comet Fish (Carassius auratus auratus) ] - Boedi Setya Rahardja; A. Shofy Mubarak; Permana Sulistyo Rini (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract The development of fish culture is strongly influenced by hatchery technology, especially in the stock of fish seed. Often, the problem arises in the stock of seeds, due to the maturation of gametes, broadstock fish sometimes do not happen simultaneously, one of alternative solution to the problem through the application of reproductive biotechnology, is preservation of sperm (Dirjennak, 2007). Preservation sperm is to optimize the male broadstock (Dirjennak, 2007). This storage process requires diluent and cryoprotectant material that could sustain sperm motility (Zaenab, 2007). Diluent material is used to reduce the activity of spermatozoa that inhibit energy usage and prolong the life of sperm (Rustidja, 2000). The use of honey as a diluent material is expected to support the vitality of spermatozoa. Material of honey there are various combinations of materials a simple sugar and salt ions. With the combination of basic ingredients and simple sugar salt ions spermatozoa can produce an energy source so it can defend itself and can fertilize an egg cell after Cryoperservation process. The purpose of this research is to know the effect of adding extender honey in enhancing sperm motility and viability of fish comet after the freezing process and to determine the best dose of honey in the process of freezing sperm comet fish (Carassius auratus auratus). This research was conducted at the Laboratory Center for Artificial Insemination Singosari. The design use Completely Randomized Design (CRD) followed by Duncan's multiple range test. Test materials in this research is sperm comet fish are packed in mini straw and stored in liquid nitrogen container with 9 treatments and 3 replications. Media diluent used was physiological NaCl is added to honey, glucose, fructose, and Tris Aminomethane. Honey dosages of the experiments were 0.3% (A); 0.4% (B), 0.5% (C), 0.6% (D) and 0.7% (E) and 0.05% glucose (KG); fructose 0.05% (KF), Tris Aminomethane (KT) and without the addition of physiological NaCl (KN). The main parameters of observed percentage of live sperm and duration of motion. The supporting parameters measured were fresh sperm concentration, percentage of live sperm fresh, long fresh sperm, pH, volume and color of sperm. The results of the research shows that the addition of honey with different dosage at diluents material physiological NaCl gived significant effect (P <0.05) against the percentage of sperm motion and long life. Average percentage of long life and highest sperm obtained by treatment of the addition of honey 0.6% (D), ie 63.89% and 101.33 seconds. Average lowest percentage of life gained by treatment of honey 0.3% (C) that were 39.67 second while the lowest was in motion treatment control without the addition of (KN) that were 28.33 seconds.